PROFIL ASSESSMEN AUTENTIK PADA GURU-GURU DI SMP NEGERI SE-KOTA MATARAM - Nur Lestari; I Wayan Mertha; Kusmiyati Kusmiyati (Postgraduate, University of Mataram, 2019)
Based on the authentic guidelines for junior high school teachers, the assessment focuses on how assessment can improve the abiolity of students in teaching and learning process to be carried out through three approaches: “Assessment of Learning, Assessment for Learning, Assessment as Learning.” This is in fact in the field of state junior high school educators need to know the authentic assesment profile that is applied based on the 2013 curriculum. The purpose of this study is to detrmine the ability and skills to carry out authentic assesment during the learning processes, to determine learning success and improvement of learning, or as a way to find out the implementation of 2013 curriculum authentic assessment profile for junior high school teachers in Mataram. The type of research used is descriptive with a survey approach. The time of the study was carried out from the end of May to October 2018. Subjects were biology teachers in junior high schools in Mataram, SMP Negeri 2, 4 and SMP Negeri 13 Mataram. Techniques for collecting data is qualitative/descriptive with questionnaires, documents, and interviews: The profile and ability to develop authentic cognitive domain assessments was carried out reaching to 100% of 21 integrated science (Biology) teachers of Junior High School in Mataram which were compiled and implemented in Daily Task inform of essay/subjectively structure and objective questions (multiple choice) reaching up to 90% according to the 2013 curriculum based on Minister of Education and Culture no. 22 of 2016. The profile and ability to develop psychomotoric assessment was compiled and implemented by 21 integrated science (biology) teahers of Junior High School in Mataram in form of practicum &work performance reachingup to 97% and modification of teachers/students textbook reach up to 85 %categoried as very good. The profile and ability to develop assessment in affective domain was implemented with techniques and instruments in form of attitude and self-assessment that reached 90% with very good categories (exactly the same as the format of the assessment guidelines) in accordance with the 2013 curriculum and modification forms reached up to 27% categoried as very less. Teachers ability needs to be developed, instrument assessment techniques need to be improved. Data were analyzed descriptivelyKeyword: Assessment, Autenthic, Profile